2022
DOI: 10.1155/2022/1019029
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability during Auricular Acupressure at Heart Point in Healthy Volunteers: A Pilot Study

Abstract: Heart rate variability (HRV) is the variation in time between each heartbeat. Increasing HRV may contribute to improving autonomic nervous system dysfunctions. Acupuncture stimulation through the vagus plexus in the ear is considered as a method that can improve HRV. In this pilot study, we examined 114 healthy volunteers at the Faculty of Traditional Medicine, University of Medicine and Pharmacy at Ho Chi Minh City, from January to May 2020. During a 20-minute interval, participants were stimulated two times … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Acupuncture can modulate the activity of the circulating system. Trinh et al 29 applied acupuncture on the left ear of healthy subjects to measure the effect of acupuncture on HRV. They discovered that HRV from the healthy subjects with acupuncture is higher than that from the healthy subjects without acupuncture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acupuncture can modulate the activity of the circulating system. Trinh et al 29 applied acupuncture on the left ear of healthy subjects to measure the effect of acupuncture on HRV. They discovered that HRV from the healthy subjects with acupuncture is higher than that from the healthy subjects without acupuncture.…”
Section: Discussionmentioning
confidence: 99%
“…They discovered that HRV from the healthy subjects with acupuncture is higher than that from the healthy subjects without acupuncture. 29 Previous study reported that electroacupuncture on LI11 (Quchi) can inhibit the rise of arterial blood pressure by reducing sympathetic nerve activity in the rat model. 30 These studies emphasize the feasibility of using acupuncture to increase HRV.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study investigating the effects of sympathetic nerve points revealed the activation of the parasympathetic nervous system, suggesting a positive effect on autonomic nervous system regulation. [53]…”
Section: Discussionmentioning
confidence: 99%
“…HR and HRV assessments were conducted as previously described [ 19 ]. Participants rested for ten minutes before HR and HRV monitoring commenced.…”
Section: Methodsmentioning
confidence: 99%